2020
DOI: 10.1186/s12889-020-09386-x
|View full text |Cite|
|
Sign up to set email alerts
|

Social marketing interventions to promote physical activity among 60 years and older: a systematic review of the literature

Abstract: Background Falls are a significant source of morbidity in people aged 65 and over, affecting one in three people in this age group. The scientific evidence indicates that physical activity is the most effective method for preventing falls among seniors. Although public health professionals often use social marketing to design and plan successful interventions, its use to promote physical activity and prevent falls among older people remains low. This article aims to provide a new systematic literature review o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 51 publications
0
11
0
2
Order By: Relevance
“…Few strategies used so far did not apply all the seven benchmark criteria ( 49 ). Fujihira et al ( 41 ) and Goethals et al ( 49 ) have showed that as a program frequently uses the social marketing benchmark criteria defined by Andreasen, it becomes more and more effective at changing the behaviors of its target population. Other reviews ( 18 , 19 , 50 ) have used the same classification criteria as Andreasen and reported similar findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few strategies used so far did not apply all the seven benchmark criteria ( 49 ). Fujihira et al ( 41 ) and Goethals et al ( 49 ) have showed that as a program frequently uses the social marketing benchmark criteria defined by Andreasen, it becomes more and more effective at changing the behaviors of its target population. Other reviews ( 18 , 19 , 50 ) have used the same classification criteria as Andreasen and reported similar findings.…”
Section: Discussionmentioning
confidence: 99%
“…Although this method has proven its worth in these other contexts, its use in getting older adults to take part in regular PA remains limited ( 41 ).…”
Section: Introductionmentioning
confidence: 99%
“…La finalidad del marketing social es atender las necesidades y demandas del grupo de audiencia con la ayuda de los principios y técnicas del marketing comercial y difundir entre ellos el comportamiento deseado, reduciendo los obstáculos y animándolos a realizar un comportamiento social. En términos más simples, el mercadeo social es la aplicación de técnicas en temas sociales para motivar a las personas a ejecutar acciones o comportamientos que en última instancia son beneficiosos para ellos (Kotler y Roberto, 1992;Goethals et al, 2020).…”
Section: Fundamentación Teóricaunclassified
“…30 With regard to health promotion, a recent systematic review has shown that the use of social marketing strategies was effective in increasing participation in, or the level of physical activity among older adults. 31 The Behaviour Change Wheel 32 (BCW) is a model created from a review of frameworks for social marketing. Based on this model, it is possible to identify, for the first time, how elderly people perceive their capability, opportunity and motivation to adopt cognitive health promoting behaviours.…”
Section: Open Accessmentioning
confidence: 99%
“… 30 With regard to health promotion, a recent systematic review has shown that the use of social marketing strategies was effective in increasing participation in, or the level of physical activity among older adults. 31 …”
Section: Introductionmentioning
confidence: 99%